P035 Improving quality of patient care in a SRH service: Introduction of endometrial biopsy for women with persistent bleeding problems. (30th June 2016) - Aziz, Najia; Mukhopadhyay, Sujit; Bashford, Claire
Abstract : Background/introduction: National Institutes of Clinical Excellence (NICE) recommends to undertake endometrial biopsy (EB) sample in cases of persistent intermenstrual bleeding and in woman aged 45 or over with failed or ineffective treatment of heavy menstrual bleeding. Since January 2015 we introduced EB in our sexual health clinics. Aim(s)/objectives: The aim was to perform a transvaginal ultrasound (TVS), undertake sexually transmitted infection (STI) screen and offer MIRENA®-IUS or other treatment options for persistent bleeding problems. This one-stop-service was meant to decrease referrals to the gynaecological service and improve a patient's journey. Methods: Retrospective analysis of all patients who underwent an EB over the past year was performed. Inclusion criteria were those specified by NICE. The exclusion criterion was postmenopausal bleeding. Results: Out of 300 patients who had a TVS (for bleeding or pain), 37 qualified for an EB. 8% of patients had additional risk factors for endometrial cancer. 2 patients had a positive STI screen and were treated. 11% of patients had chronic endometritis on EB and the rest of the biopsies were negative. 54% of patients had a MIRENA®-IUS inserted at the same visit. 78% of patients were discharged on the same day of consultation. Discussion/conclusion: Our study demonstrates that irregular bleeding problems in women presenting to sexual health clinics can be managed effectively in the same sitting. The clinician needs to be trained in TVS and EB procedures. This reduces the number of women referred to the gynaecological department for persistent bleeding problems.